White light modulated forming-free multilevel resistive switching in ZnO:Cu films - Saini, Mahesh; Kumar, Mohit; Mandal, Rupam; Mitra, Anirban; Som, Tapobrata (Applied Surface Science, 2021)
Optical wavelength controlled forming-free, multilevel resistive switching (RS) is investigated in pulsed laser deposited visible light active 2 wt% Cu-doped ZnO (CZO) thin films. The illumination of wavelength-specific visible light in conjunction with applied voltage modulates the bipolar switching behaviour. Here the control of current compliance is the key to enable the memory device work reversibly at different operating voltage (<10 V) windows. The “set”/“reset” voltages for RS obtained for different wavelengths (in the range of 300–700 nm) appear in between the “set”/“reset” voltages obtained under dark and white light illumination. Light wavelength adds up an extra control parameter in conventional memristor devices for the encryption/decryption of specific information offering better cybersecurity. The RS mechanism is suggested to be filamentary where the formation and the rupturing of conducting filament occur by the migration of defects (e.g. O vacancies and interstitial Zn atoms) under externally applied electric field. This study provides a new insight towards designing visible light-controlled electrically-driven memristive devices, useful for low power operation, for neuromorphic computing.
Keywords: Cu-doped ZnO; Current compliance; I-V characteristic; Multilevel resistive switching; Optical wavelength; Reset voltage; Resistive switching; Visible light; White light; ZnO:Cu films; Cu-doped ZnO; Current compliance; I-V characteristics; Resistive switching; Visible light